Profile of Science Literacy Skills of Junior High School Students in Surabaya City - Hidayati, Siti Nurul (Jurnal Pijar Mipa, 2025)
Science literacy is critical for every student to master because it can train students' ability to think critically, solve problems, and understand scientific phenomena in everyday life. This study aims to describe the initial science literacy skills of students in Surabaya junior high schools. This research design is a survey design with data analysis techniques used descriptive quantitative, namely by analyzing the average percentage of 3 indicators of science literacy competencies, including 1) explaining phenomena scientifically, 2) evaluating and designing scientific investigations, and 3) interpreting data and evidence scientifically. The research instrument consisted of 9 science literacy test questions adopted from the 2015 PISA science literacy test. The subjects of this research were the 8th-grade students of Labschool UNESA 1 Surabaya Junior High School, consisting of 99 students, 44 male and 55 female students. The results showed that the indicators of evaluating and designing scientific investigations and interpreting data and evidence scientifically obtained a moderate category with an average of 42% and 41%. The Indicator of explaining phenomena scientifically still requires additional training because it is included in the low category with an average of 40%. This is due to students' inability to analyze information, conclude, and link theories with tangible phenomena. Based on the study results, it can be concluded that grade VIII students in Surabaya Junior High Schools have moderate science literacy skills with an overall average percentage of 41%.